MRI for diagnosis of axial spondyloarthritis: major advance with critical limitations 'Not everything that glisters is gold (standard)'. Issue 1 (12th January 2018) - Lukas, Cédric; Cyteval, Catherine; Dougados, Maxime; Weber, Ulrich
Abstract : Recognition of axial spondyloarthritis (SpA) remains challenging, as no unique reference standard is available to ascertain diagnosis. Imaging procedures have been used for long in the field, in particular pelvic radiography, to capture structural changes evocative of sacroiliitis, the key feature in SpA. The introduction of MRI of the sacroiliac joints (SIJs) has led to a major shift in recognition of the disorder. MRI has been shown to detect the initial inflammatory processes, in particular osteitis depicted by bone marrow oedema, even in patients having not yet developed structural lesions. In addition, MRI has revealed a previously under-recognised very early clinical phase of the disease where patients have symptomatic axial involvement, but no structural changes. However, what constitutes a 'positive MRI' in SpA remains controversial, since both sensitivity and specificity show limitations, and interpretation of MRI lesions in daily practice is critically dependent on the clinical context. There is growing evidence that integration of the assessment of structural changes on dedicated T1 weighted-sequences on MRI may enhance diagnostic utility. The performance of MRI in detecting structural lesions in the SIJs may even be superior to traditional evaluation by pelvic radiography. These findings launched a debate on imaging in SpA, whether MRI, which is advancing early recognition of disease and shows superiority to detect structural changes, should replace traditional conventional radiography of the SIJs.